Empathic Accuracy and Behavioral Empathy After a Moderate Dose of Beer - Isabelle Cristina Baltariu; Violeta Enea; Teresa B. Prucker; Marije aan het Rot (Human Psychopharmacology: Clinical and Experimental, 2026)
ABSTRACT Objectives Empathic accuracy (EA) represents a person's ability to correctly infer the emotions of another person. One past study in men found lower EA for positive emotions after a moderate dose of hard liquor compared to after placebo, particularly among non‐hazardous drinkers. The present study aimed to replicate this finding, using a moderate dose of beer and a mixed design. Moreover, we added a novel measure of behavioral empathy. Methods Participants (62% men) completed the Alcohol Use Disorders Identification Test, Empathy Quotient, and Revised Drinking Motives Questionnaire. Before and after drinking either beer (6.6% alcohol, n = 28) or its 0.0% equivalent (placebo, n = 38), they watched videoclips of targets talking about emotional autobiographical events and rated how targets felt while talking. Behavioral empathy was assessed by presenting participants with painful scenarios and asking whether they would help the people in pain. Results The previous finding of lower EA for positive emotions after alcohol was not replicated. Nonetheless, after alcohol non‐hazardous drinkers were less willing to help people in pain. Trait affective empathy (i.e., a person's long‐term disposition to experience emotional responses congruent to another's feelings) and the drinking to cope motive did not significantly moderate the findings. Conclusions Although alcohol may alter empathy, its effects are not consistent and may depend on the dose and type of alcohol consumed. The moderating roles of trait empathy and trait aggressivity deserves further study.